Comparison of metabolites in the follicular fluid of bovine preovulatory and cystic ovarian follicles using nuclear magnetic resonance - SINGH, MANDEEP; HONPARKHE, MRIGANK; KUMAR, AJEET; SINGHAL, SUMIT (The Indian Journal of Animal Sciences, 2018)
Estimation of metabolites in cystic and normal preovulatory follicular fluid through proton Nuclear Magnetic Resonance (1H NMR) in cattle suffering from cystic ovarian follicle is highly desirable.The trans-vaginal ultrasound guided ablation was used to collect follicular fluid from cystic (15) and normally cycling (8) dairy cattle. NMR spectra of both fluids were recorded at a resonance frequency of 500.13 MHz on a Bruker Avance-500 spectrometer equipped with solid state probe (5 mm). Spectra were phased manually, baseline corrected, and calibrated against 3-(trimethylsilyl) propionic-2,2,3,3-d4 acid at 0.0 parts per million (ppm) using Prometab software running within MATLAB. The cystic ovarian follicle associated metabolites with variable importance in projection (VIP) scores >2 were lactate (1.98 ppm), UDP-G (5.62), pyruvate (2.34 and 2.38) and creatinine/creatine (3.14) in cystic and normal preovulatory follicular fluid.These metabolites showed identifiable peaks, and thus can be used as potential biomarkers for dairy cattle suffering from cystic ovarian follicle.